2018
DOI: 10.5937/ekopolj1802757v
|View full text |Cite
|
Sign up to set email alerts
|

Applying the exponential smoothing model for forecasting tourists' arrivals: Example of Novi Sad, Belgrade and Niš

Abstract: Predicting future movements of tourism demand based solely on the past behaviour of variables such as number of overnight stays is crucial for the development of tourism and mitigation of seasonality. Nowadays, there are many different models that could be used for forecasting. Sometimes, some simpler models could fit better to collected data and, in the other hand, more sophisticated ones are more convenient. In this paper, the exponential smoothing models have been applied on the data that was taken from Rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…This is reasonable because of the observed seasonality in GCS. An exception is "PC" line where the low value of γ indicates a stable seasonal effect (Vujko, et al, 2018). For all coastal lines the Ljung -Box statistical criterion showed that the errors had white noise behavior and the models were adequate.…”
Section: Analysis and Resultsmentioning
confidence: 95%
“…This is reasonable because of the observed seasonality in GCS. An exception is "PC" line where the low value of γ indicates a stable seasonal effect (Vujko, et al, 2018). For all coastal lines the Ljung -Box statistical criterion showed that the errors had white noise behavior and the models were adequate.…”
Section: Analysis and Resultsmentioning
confidence: 95%
“…This is reasonable given the observed seasonality in the GCS. For the rest of the ports the low value of γ indicates a stable seasonal effect [53]. The port of Gavdos was the only one that gave DMTS.T + S.A as the best model.…”
Section: Resultsmentioning
confidence: 97%
“…According to Papić-Blagojević et al (2016), and Vujko et al (2018), seasonality is one of the main aspects affecting tourism, and forecasts of tourist arrivals are essential for planning (Brougham & Butler, 1981), policy making (Dogan, 1989;Canizares et al, 2016) and budgeting purposes by tourism operators (Choi & Murray, 2010;Deng et al, 2011;Gounopoulos et al, 2012). Ada Ciganlija is a river island on Sava River and popular swimming area for residents of Belgrade during the summer, but it attracts a significant number of visitors off summer season, so, as such, it represents one of the favorite zones of picnic-recreational tourism within the city of Belgrade.…”
Section: Introductionmentioning
confidence: 99%